Withania somnifera Extract Protects Model Neurons from In Vitro Traumatic Injury. Issue 7 (July 2017) - Saykally, Jessica N.; Hatic, Haris; Keeley, Kristen L.; Jain, Subhash C.; Ravindranath, Vijayalakshmi; Citron, Bruce A.
Withania somnifera has been used in traditional medicine for a variety of neural disorders. Recently, chronic neurodegenerative conditions have been shown to benefit from treatment with this extract. To evaluate the action of this extract on traumatically injured neurons, the efficacy of W. somnifera root extract as a neuroprotective agent was examined in cultured model neurons exposed to an in vitro injury system designed to mimic mild traumatic brain injury (TBI). Neuronal health was evaluated by staining with annexin V (an early, apoptotic feature) and monitoring released lactate dehydrogenase activity (a terminal cell loss parameter). Potential mechanisms underlying the observed neuroprotection were examined. Additionally, morphological changes were monitored following injury and treatment. Although no differences were found in the expression of the antioxidant transcription factor nuclear factor erythroid 2-like 2 (Nrf2) or other Nrf2-related downstream components, significant changes were seen in apoptotic signaling. Treatment with the extract resulted in an increased length of neurites projecting from the neuronal cell body after injury. W. somnifera extract treatment also resulted in reduced cell death in the model neuron TBI system. The cell death factor Bax was involved (its expression was reduced 2-fold by the treatment) and injury-induced reduction in neurite lengths and numbers was reversed by the treatment. This all indicates that W. somnifera root extract was neuroprotective and could have therapeutic potential to target factors involved in secondary injury and long-term sequelae of mild TBI.